Latin Translations of Greek Texts from the 11th to the 13th Century - Bara, Péter,; Toma, Paraskevi, (Late Antiquity and Medieval Studies E-Books Online, Collection 2024., 2025)
This volume examines the 'phenomenon' of translation from Greek into Latin from the eleventh century to the thirteenth. These translated texts prompted Western scholars to rediscover the works of classical Greek and Byzantine authors and reshape the medieval intellectual landscape. Though our agenda focuses on translations of scientific texts, the collection of essays here also offers the reader insights into the broader cultural, social, and political functions and implications of individual translations and translation more broadly as a practice. Contributors are Dimiter Angelov, Péter Bara, Pieter Beullens, Alessandra Bucossi, Luigi d'Amelia, Paola Degni, Michael Dunne, Elisabeth Fisher, Brad Hostetler, Estelle Ingrand-Varenne, Marc Lauxtermann, Tamás Mészáros, James Morton, Teresa Shawcross, and Anna Maria Urso.